Evaluation of pelvic floor muscle elasticity in patients with overactive bladder syndrome using real-time tissue elastography. (September 2022) - Abe-Takahashi, Yui; Kitta, Takeya; Ouchi, Mifuka; Chiba, Hiroki; Higuchi, Madoka; Togo, Mio; Shinohara, Nobuo
Abstract: Introduction and hypothesis: The purpose of this study was to compare the muscle elasticity of the striated urethral sphincter (SUS) using real-time tissue elastography (RTE) as an evaluation of pelvic floor muscle (PFM) function between overactive bladder (OAB) patients and healthy women. Methods: The subjects were 8 healthy middle-aged women (healthy group; age range 57–65 years) and 9 female OAB patients (OAB group; age range 42–80 years). The target sites of elastography were the striated urethral sphincter (SUS) and adipose tissue as the reference site; muscle elasticity was calculated as the strain ratio (SR) of the SUS to the reference site. Evaluations were performed at rest and during PFM contraction. The OAB group completed OAB symptom and quality of life questionnaires. The SUS SR was compared between the groups. The SUS SR at rest and during PFM contraction was compared within groups using the t -test and Wilcoxon's test. The relationship between the questionnaire results and the SUS SR was evaluated by correlation analysis. Results: Intergroup comparisons between the healthy and OAB groups showed no significant differences in SUS SR at rest and during PFM contraction. On intragroup comparisons, the SUS SR was significantly higher during PFM contraction than at rest in the healthy group (p = 0.011); in the OAB group, there was no significant difference in the SUS SR between rest and PFM contraction. The SUS SR was not significantly correlated with questionnaire results for OAB symptoms. Conclusion: This study shows the potential to non-invasively confirm the inability of OAB patients to correctly perform PFM contraction using RTE.